A survey of birth order status of students studying for medical degree at the University of Sheffield. (11th August 2014) - Clayton, Sarah; Apperley, Elizabeth; Hannon, Fergus; Karia, Anika; Baxter, Victoria; Julious, Steven A
Summary: Objective: It is hypothesised that firstborn children and only children are more intelligent with higher intelligence scores having been observed in firstborn or only children. Evidence of the increased intelligence has been suggested by the fact that 21/23 (91%) of US astronauts, 23/43 (53%) of US presidents and between 75 and 80% of students at Harvard are firstborn or only children. It is of interest to investigate, therefore, whether a high achieving career such as medicine has a disproportionate number of firstborn or only children. Design: A survey of medical students. Setting: The University of Sheffield Medical School. Participants: All students studying medicine in the academic year 2011–2012. Main outcome measures: The proportion of firstborn or only children. Results: There was a disproportionate number of students who were firstborn or only children: 53% (95% CI 49 to 58%). The expected percentage is 39.8% and therefore we can reject the null hypothesis. The results were consistent across all phases of study. Conclusions: There is a higher than expected proportion of medical students at the University of Sheffield who are firstborn or only children. The data though highlight the issue of comparing populations. Here we are comparing a population of medical students with a general population. A comparison which may not be appropriate as medical students may be drawn from a subsample of the general population.